Sistem Pelayanan Pelanggan Berbasis Customer Relationship Management dengan Pendekatan UX pada Toko Na Roti - Masayu Wianda Putri; Aninda Muliani Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Customer service plays an essential role in maintaining customer loyalty in retail businesses. However, customer service processes at Toko Na Roti are still managed conventionally, resulting in inefficient customer data management, promotional activities, transaction history management, and complaint handling. This study aims to develop a Customer Relationship Management (CRM)-based Customer Service Information System using the Laravel Framework and MySQL by implementing the UX Design Process to ensure that the system meets user requirements. The UX Design Process consisted of the Empathize, Define, Ideate, Prototype, and Test stages, which identified user requirements and produced six main system modules, namely customer management, transaction history, promotion management, complaints and feedback, a rule-based chatbot, and an owner analytics dashboard. The system was implemented using the Laravel Framework as the development framework and MySQL as the database management system. Functional testing was conducted using the Blackbox Testing method across 10 test scenarios representing all core system functionalities. The testing achieved a 100% success rate, indicating that all system modules operated according to the predefined functional requirements. The developed system supports more structured customer relationship management, facilitates the digitalization of customer services, and provides data-driven information to support managerial decision-making at Toko Na Roti.